Neighbourhood fluorosis in people residing in the vicinity of superphosphate fertilizer plants near Udaipur city of Rajasthan (India) - Choubisa, Shanti Lal; Choubisa, Darshana (Environmental monitoring and assessment, 2015)
Chronic industrial fluoride toxicosis in the forms of dental, skeletal and non-skeletal fluorosis was investigated in 162 villagers (94 males and 78 females) above 15 years of age living in the vicinity of superphosphate fertilizer plants located approximately 12 km south of Udaipur city of Rajasthan, India. Out of these villagers, 90 (55.5 %) and 29 (18.0 %) were found to be afflicted with mild to severe dental and skeletal fluorosis, respectively. Dental fluorosis characterized with light to deep-brownish bilaterally striated horizontal lines, pits or patches and fine dots or granules was noted on incisor teeth of villagers. Irregular wearing, excessive corrosions (abrasions), dark-brownish pigmentation of exposed cementum and dentine material, diastem as between teeth, pronounced loss of tooth supporting bone with recession and bulging of gingiva (gum) were also present in subjects of older age group (>55 years). Among 29 (18.0 %) individuals, mild to moderate manifestations of skeletal fluorosis such as crippling, kyphosis, invalidism and genu-varum syndrome were found. In these fluorotic subjects pain/rigidity in major joints viz. neck, back, hip, knee and shoulder was also found. None of the fluorotic subjects showed evidence of genu-valgum syndrome. Other signs of chronic industrial fluoride intoxication in soft tissues (non-skeletal fluorosis) included colic, intermittent diarrhoea or constipation, bloating, polyuria and polydipsia. These findings indicate that surrounding environment of superphosphate fertilizer plants is contaminated with fluoride emission, which in turn is causing diverse ill health effects in humans which are discussed.